Adsorption of uremic toxins over dealuminated zeolites - Bachar Koubaissy; Joumana Toufaily; Zainab Yaseen; T Jean Daou; Safi Jradi; Tayssir Hamieh (Adsorption Science & Technology)
In this study, adsorption capacities of uremic toxins over Faujasite (HFAU) and Beta (HBEA) have been evaluated by varying the composition of solvent by using water, physiological, and sodium chloride solutions. HFAU was found to be more efficient in adsorption of these molecules. The adsorption results over HFAU were compared in various conditions to understand the adsorption mechanism. Thus, the adsorption mechanism was confirmed also by Fourier transform infrared and X-ray diffraction analysis, and it is found to be through the interaction of creatinine by hydrogen bonding on two types of sites on zeolites. Pseudo-second-order equation described well the adsorption kinetics data. Equilibrium isotherms were determined by Fowler–Guggenheim model. Finally, hydrophobic HFAU zeolite seems to be an efficient adsorbent; it is able to be easily regenerated under air, through retention of these initial adsorption properties.